#### Answer

$g=\frac{s-vt}{t^2}$

#### Work Step by Step

$vt + gt^2 = s$
$gt^2 = s-vt$
$g=\frac{s-vt}{t^2}$

Published by
Pearson

ISBN 10:
0-13446-914-3

ISBN 13:
978-0-13446-914-0

$g=\frac{s-vt}{t^2}$

$vt + gt^2 = s$
$gt^2 = s-vt$
$g=\frac{s-vt}{t^2}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.